Hydrostatic bearing circular recess damping characteristic effectiveness on rotor vibration - Seperamaniam, Thandayuthapani; Abdul Jalil, Nawal Aswan; Zulkefli, Zamir Aimaduddin; As'arry, Azizan (Malaysian Tribology Society, 2018)
The paper evaluates the hydrostatic bearing circular recess design selection criteria for an experiment analysis for dynamic response characteristic of rotor-bearing system, incorporated with single pocket recess hydrostatic bearing and orifice compensation. Evaluation of the circular recess hydrostatic bearing design parameter was conducted with comparing experimental values, pressure variation externally pressurized fluid in recess for 0.7 bar and 1 bar, magnification factor, frequency ratio, damping ratio and damped vibration criteria. Numerical values of the bearing design parameter for damping coefficient (Cb) were compared with the experiment damping coefficient (Cc). The hydrostatic bearing of circular recess damping coefficient prediction gives expectable argument less than 5 % variation accuracy with experiment damping coefficient (Cc).